Study on the direction of artificial intelligence technology based on network evolution - Zhen YANG; Jianjun ZHAO; Yongjun HUANG; Jie LI; Nan CHEN (Dianxin kexue)
The national strategy positions artificial intelligence (AI) and Internet of things (IoT)/5G as important components of information technology facilities at the same time.Among them, AI belongs to new technology infrastructure, and IoT/5G belongs to communication network infrastructure.It leads to the technical direction of “integrate and develop communication and AI technology”.For telecom operators, how to integrate AI technology with the network, reconstruct network technology architecture, and open “AI ability” as a “service” will be an important technology evolution direction.Based on this proposition, the development direction of AI and network technology in the future was discussed, and a reference idea for the integration development and application direction of AI technology with the network architecture of IoT/5G in the future was provided.